MiR-155-5p Implicates in the Pathogenesis of Renal Fibrosis via Targeting SOCS1 and SOCS6. (8th June 2020) - Zhang, Wanfen; Li, Xiaoping; Tang, Yushang; Chen, Cheng; Jing, Ran; Liu, Tongqiang
Abstract : Renal fibrosis is associated with the reduction in the functional renal parenchyma and in most cases progresses to end-stage kidney failure, a devastating condition that requires lifelong dialysis or kidney transplantation. However, due to the extreme complexity in the pathogenesis of renal fibrosis and our limited knowledge, therapeutic options for renal fibrosis in the clinical setting are still scarce and often ineffective. Hence, further studies on the molecular mechanisms underlying renal fibrosis are compellingly needed. Multiple miRNAs have demonstrated to participate in kidney diseases in a TGF- β dependent or independent manner, but there is very little known about miR-155-5p on renal fibrosis. In the present study, we firstly explored the expression level and functions of miR-155-5p in the setting of renal fibrosis. Our research revealed that miR-155-5p is highly expressed in kidney tissues from patients and unilateral ureteral obstruction (UUO) rat models, and miR-155-5p knockdown significantly blocks renal fibrosis both in vivo and in vitro . In mechanism, our data demonstrate that miR-155-5p promotes renal fibrosis by increasing the phosphorylated activation of STAT3 via targeting SOCS1/6. Altogether, our findings highlight a miR-155-5p/SOCS/STAT3 axis in the pathogenesis of renal fibrosis, which may provide promising therapeutic targets for clinical prevention of this disease.